Different Sepsis Patient Outcomes Due to Multidrug-Resistant Organisms (MDRO): A Study of Empirical Antibiotic Sensitivity Test Results - Fadrian, Fadrian; Ahmad, Armen; Harvindra, Astrid; Putri, Vidola Yasena (Faculty of Medicine, Universitas Tadulako, 2025)
Background: Sepsis, a severe immune response to infection, has a concerning global mortality rate of 85%, predominantly due to Gram-negative bacteria. The rise of antibiotic resistance in these organisms complicates treatment, leading to higher mortality and prolonged hospital stays. Effective empirical antibiotics can mitigate these outcomes. Objective: This study compares outcomes of sepsis patients infected with multidrug-resistant organisms (MDRO) based on empirical antibiotic sensitivity testing, focusing on mortality and length of stay (LOS) within 14 days of sepsis onset. Methods: A prospective cohort observational study at Dr. M. Djamil General Hospital included 94 participants. Patients who died within 14 days were excluded from the LOS analysis to prevent bias. Initial assessments included culture sampling and organ dysfunction. Results: The study revealed no significant difference in mortality based on antibiotic sensitivity (p=0.283), but the LOS was significantly shorter in those treated with sensitive antibiotics (p<0.016). Conclusion: LOS was significantly affected by antibiotic sensitivity, with patients receiving effective antibiotics experiencing shorter stays, though mortality differences were not statistically significant in the 14-day window